ChemInform Abstract: DMC‐Mediated One‐Pot Synthesis of Biaryl Ketones from Aryl Carboxylic and Boronic Acids. Issue 31 (11th July 2013) - Pathak, Arunendra; Rajput, Chatrasal S.; Bora, Pushkar S.; Sharma, Somesh
Abstract Carboxylic acids, activated in situ with DMC, undergo Pd‐catalyzed cross‐coupling reaction with arylboronic acids to produce unsymmetrical aromatic ketones.